1992
DOI: 10.1097/00000658-199205000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Significant Trends in the Treatment of Hepatic Trauma Experience With 411 Injuries

Abstract: Several significant advances in the treatment of hepatic injuries have evolved over the past decade. These trends have been incorporated into the overall treatment strategy of hepatic injuries and are reflected in experiences with 411 consecutive patients. Two hundred fifty-eight patients (63%) with minor injuries (grades I to II) were treated by simple suture or hemostatic agents with a mortality rate of 6%. One hundred twenty-eight patients (31%) sustained complex hepatic injuries (grades III to V). One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
18

Year Published

1994
1994
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(100 citation statements)
references
References 43 publications
2
79
0
18
Order By: Relevance
“…ALT Liver injury may lead to death as a result of uncontrolled bleeding or sepsis (5,20). Non-operative management of stable liver trauma patients is associated with reduced mortality (21,22). However, it is important to recognize traumatic liver devascularization since an initially stable patient may decompensate due to septic complications.…”
Section: Discussionmentioning
confidence: 99%
“…ALT Liver injury may lead to death as a result of uncontrolled bleeding or sepsis (5,20). Non-operative management of stable liver trauma patients is associated with reduced mortality (21,22). However, it is important to recognize traumatic liver devascularization since an initially stable patient may decompensate due to septic complications.…”
Section: Discussionmentioning
confidence: 99%
“…The line of management of isolated liver trauma is primarily guided by the hemo-dynamic status of the patient at the time of presentation in emergency department and response to the initial fluid challenge. Surgery is considered for isolated liver injury if the volume of replacement is more than 40ml/kg during first few hours [8][9]. A surgeon performed ultrasound using a 3.5 MHz transducer is an effective techniques for rapid imaging in hepatic injury [10].…”
Section: Discussionmentioning
confidence: 99%
“…6 In humans, 30 minutes of PTO has been accepted as a safe procedure, and is usually employed in liver surgery. 7 More recently, Fontelles et al 8 demonstrated a clear correlation among hemodynamic and metabolic variables in rats subjected to hemorrhagic shock followed by 15 minutes of PTO; although not focused on mortality, the study points out the continued relevance of PTO in the surgery of trauma. On the other hand, selective portal vein occlusion (SPVO) may be achieved by means or ligation of the vein 1 .…”
Section: Introductionmentioning
confidence: 92%